A preliminary assessment of China’s Belt and Road Initiative (BRI) as an economic diplomacy strategy and its impact on national-EU political dynamism in Europe. - Soo, Shet Yuan; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This research is to conduct a preliminary assessment on the Belt-and Road Initiative (BRI), an international co-operation framwork proposal announced by PRC in 2013, from the perspective of Economic Diplomacy (ED) and Economic Statecraft (ES). The research focuses on the twofold political-economic impact BRI is already having both in PRC and Europe, illustrating the fact that, due to the twofold nature of BRI, it should be studies and analyzed from the perspective of Economic Diplomacy (ED) in order to sufficiently address both its political and economic impacts. However, due to the lack of mutual understanding and agreement over a wide range of complicated issues, including the lack of mutual agreement over the topic of ED and ES, the uneven level of development in ED and ES studies, mutual ignorance and misconception regarding other parties’ political and economic traditions and practices, etc, BRI, in its current form and progression, is risking to become a “white elephant” project without concrete co-operation plan. In order for BRI to succeed, significant efforts and sacrifices must be made by the various actors, yet given the exisitng all-encompassing scope of BRI as proposed by PRC, it is unlikely that any of the pary has the necessary resources and motivations to promote the initiative. Thus, BRI (in its current form) is increasingly possible to become an overly ambitious policy proposal which is unable to fulfil its proposed goals, both domestically and internationally
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses